Konsep Toleran Dalam Pendidikan Islam Prespektif KH.Abdurrahman Wahid - Lucky Damara Yusuf; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2023)
Islamic education concept Tolerance is an educational concept that is centered on the interests of the participants education and in accordance with the development and potential it has so that The critical power of students is awakened which leads to the creation of human beings freedom in accordance with the natural nature of humanity. The concept of Islamic education of tolerance from the perspective of K.H. Abdurrahman Wahid.It is hoped that this will become a reference for education activists as a concept that is able to create tolerance so that students are free to study the development of science both from the west and from the east without must be uprooted from its local roots.